Banking Ecosystems: Development Specifics - V. D. Smirnov (Управленческие науки)
The topic of the research is the phenomenon of ecosystems created by banks, as well as related technological innovations introduced by credit institutions in order to increase their efficiency and obtain new opportunities for cooperation with non-financial organizations. One of the strategically important management decisions which affect the bank's business model is to determine the specifics of ecosystem growth. The study's goal is to figure the optimal balance between traditional activities and non-banking services of credit institutions. This suppose to strengthen their position in the face of penetration of digital competitors into banking operations (Internet banks, financial and large technology companies, telecoms). The theoretical and methodological basis of the research was formed by the scientific works of foreign scientists and experts on improving the efficiency of banking institutions. There were used methods of qualitative and quantitative analysis of scientific publications, analytical materials of well-known consulting companies, statistical data. As a result, the author found a technological transformation is required using such approaches to customer service (retail and corporate) that reflect their needs in banking with the intensive use of relevant competencies in cash management, means and risks. That will cause to protect the banking business from digital competitors and increase its market capitalization. All these measures will be able to induce clients to use more extensively the banks opportunities and help them to increase investments in their core business, thereby contributing to its growth. The author concludes that being developed ecosystems, it is advisable for banks to focus on services close to their core work, as well as on increasing the efficiency of their own activities and providing new services. Meanwhile, the marketplaces development within the banking ecosystems does not give the latter advantages in the competition in the banking services market.